Measuring of Islamic Business Ethics in Indonesia Islamic Bank - Saori, Sopyan (Archives of Business Research, 2019)
The business characteristic of Islamic banks is the implementation of Islamic business ethics. Parallel with the trend of increasing preference to ethical institution, Islamic banks should put this as its competitive edge toward its competitor conventional competitor banks. However, only few previous studies discussed about the implementation of Islamic business ethics within Islamic banks and none suggested how to measure such implementation. This paper is a study of the literature on ethics and used descriptive qualitative methods as data analytical. The unit of analysis in this study is employees of Islamic Bank in Indonesia. This paper synthesizes the dimensions of Islamic business ethics extracted from the Quran and Sunnah, which were proposed by previous research and divided into five dimensions there are, the union of unity, balance, free will, responsibility and truth. Furthermore, this paper describes the findings through deep interviews with information. Opportunities for future empirical studies are recommended at the end of this paper.